2007
DOI: 10.1111/j.1475-2743.2007.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Water‐table management in lowland UK peat soils and its potential impact on CO2 emission

Abstract: The rate of oxidation of peat soils is highly seasonal and varies with temperature and soil moisture content. Large variations in soil moisture content result in wet–dry cycles that can enhance peat degradation. Water‐table management plays a crucial role in controlling and damping the effect of these environmental factors. However, maintaining high ditch water levels in fields bounded by ditches does not guarantee a high field groundwater level. The effect of installing subsurface irrigation at different spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 42 publications
2
20
2
Order By: Relevance
“…However, a significant and negative correlation between water table and CO 2 emission was detected in this study (Table 1). This result does not support the observation reported by many investigations, where CO 2 emissions increased following the lowering of the water table level [58]; however, it is in agreement with the results reported in Berglund and Berglund [48] and Kechavarzi et al [59], where CO 2 emission rates were higher in the peat soil with a high water table level.…”
Section: Relationship Of Environmental Factorstoghg Emissionscontrasting
confidence: 84%
“…However, a significant and negative correlation between water table and CO 2 emission was detected in this study (Table 1). This result does not support the observation reported by many investigations, where CO 2 emissions increased following the lowering of the water table level [58]; however, it is in agreement with the results reported in Berglund and Berglund [48] and Kechavarzi et al [59], where CO 2 emission rates were higher in the peat soil with a high water table level.…”
Section: Relationship Of Environmental Factorstoghg Emissionscontrasting
confidence: 84%
“…Contrary to our results, many investigations have reported increasing CO 2 emissions following lowering of the groundwater level (Eggelsman, 1976;Renger et al, 2002;Wessolek et al, 2002). Findings supporting our results, with a higher emission rate at intermediate groundwater levels compared with low (dry soil), have been reported by Davidson et al (1998), Chimner and Cooper (2003) and Kechavarzi, C. et al (2007). Nieveen et al (2005) found that the distance to the groundwater did not influence the emission of CO 2 and Aerts and Ludwig (1997) and Maljanen et al (2001) reported similar results.…”
Section: Effect Of Water Table Regulation On Emission Ratescontrasting
confidence: 52%
“…Schrier-Uijl et al (2010a) as well as Dias et al (2010) reported higher fluxes (~1 and 0.03 mg CH 4 m −2 h −1 ), but earlier work of suggest that intensively used well-drained grassland is a net sink for CH 4 (−0.003 mg CH 4 m −2 h −1 ). At the same time, these drained peatlands emit substantial quantities of CO 2 and N 2 O, and all should be included when estimating a full greenhouse gas balance (Hendriks et al 2007;Kechavarzi et al 2007;Veenendaal et al 2007). Since water may cover anywhere between 6 and 43% in these peatlands (Vermaat and Hellmann 2010), our findings imply that landscapescale assessments of methane fluxes require separate estimates of terrestrial and aquatic fluxes, where the latter need to take into account productivity and groundwater table (Kechavarzi et al 2007) of the adjacent land.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, these drained peatlands emit substantial quantities of CO 2 and N 2 O, and all should be included when estimating a full greenhouse gas balance (Hendriks et al 2007;Kechavarzi et al 2007;Veenendaal et al 2007). Since water may cover anywhere between 6 and 43% in these peatlands (Vermaat and Hellmann 2010), our findings imply that landscapescale assessments of methane fluxes require separate estimates of terrestrial and aquatic fluxes, where the latter need to take into account productivity and groundwater table (Kechavarzi et al 2007) of the adjacent land. We did a tentative landscape-scale estimate using our own aquatic CH 4 fluxes at annual mean temperature, terrestrial estimates from Dias et al (2010), and a methane emission estimate for dairy cattle from Veenendaal et al (2007).…”
Section: Discussionmentioning
confidence: 99%